2007
DOI: 10.1007/s11295-007-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mapping of a locus conferring plum pox virus resistance in two apricot-improved linkage maps

Abstract: Sharka disease, caused by the plum pox virus (PPV), is one of the major limiting factors for stone fruit crops in Europe and America. In particular, apricot is severely affected suffering significant fruit losses. Thus, PPV resistance is a trait of great interest for the apricot breeding programs currently in progress. In this work, two apricot maps, earlier constructed with the F 1 'Goldrich × Currot' (G×C) and the F 2 'Lito × Lito'-98 (L×L-98) populations, have been improved including 43 and 37 new simple se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
94
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 55 publications
9
94
3
1
Order By: Relevance
“…Minor QTL were discovered in the Polonais 9 SEO progeny in LG3 and LG5 of both SEO and Polonais [50]. The main QTL on LG1 was upheld by Sicard et al [51] establishing new microsatellite (SSR) markers flanking the QTL and by Lalli et al [52] in a backcross population of SEO 9 Vestar and was again confirmed by Soriano et al [46] in the extended F2 Lito selfed progeny. Most of the resistance determinants shown above were characterized using the PPV-D strain as a source of inoculum and, at present, the only resistances specific to the PPV-M strain are those endorsed in the BC1 SEO xVestar [52] and in P. davidiana [44].…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 87%
See 2 more Smart Citations
“…Minor QTL were discovered in the Polonais 9 SEO progeny in LG3 and LG5 of both SEO and Polonais [50]. The main QTL on LG1 was upheld by Sicard et al [51] establishing new microsatellite (SSR) markers flanking the QTL and by Lalli et al [52] in a backcross population of SEO 9 Vestar and was again confirmed by Soriano et al [46] in the extended F2 Lito selfed progeny. Most of the resistance determinants shown above were characterized using the PPV-D strain as a source of inoculum and, at present, the only resistances specific to the PPV-M strain are those endorsed in the BC1 SEO xVestar [52] and in P. davidiana [44].…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 87%
“…A first determinant was mapped on linkage group 1 (LG1) by using an F1 progeny of Goldrich 9 Valenciano [46]. These studies were also verified by a quantitative trait locus (QTL).…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 89%
See 1 more Smart Citation
“…The disease spread from its origin in the Balkan countries to most of the European subcontinent and the areas around the Mediterranean basin. It is one of the most limiting factors in apricot production and results in deformed, unripen and unmarketable fruits (Sicard et al 2008;Soriano et al 2008). The PPV epidemic also appears in Russia, India, Kazakhstan and Pakistan (EPPO Bulletin 2006), its first occurrence in Japanese apricot (P. mume Sieb.…”
mentioning
confidence: 99%
“…'SEO' is the resistant resource (Karayiannis et al 2008), but 'Goldrich' and 'Harcot' are tolerant resources to PPV (Stylianidis et al 2005). These cultivars are used as donors for resistance in conventional breeding based on the crosses between the PPV-resistant and the local cultivars susceptible to PPV virus throughout Europe (Hurtado et al 2002;Soriano et al 2008). Previous study indicates that this PPV resistance mechanism might have been directly or indirectly introduced from non-domesticated species found in China, for example P. sibirica, P. mandshurica, P. mume, P. sibirica var.…”
mentioning
confidence: 99%